Developing A Model for Teaching Speaking Using Cooperative Learning - *, Ngadiso (Proceeding of International Conference on Teacher Training and Education, 2016)
The paper is aimed at: (1) finding out the weaknesses of the existing model for teaching speaking; (2)developing a model for teaching speaking using cooperative learning; and (3) finding out whether a model for teaching speaking using cooperative learning is more effective than the existing model for teaching speaking. It is an educational research and development (R & D) for developing a model for teaching speaking using cooperative learning. The research was conducted at the first semester of English Education Department of Graduate School UNS Solo. The steps consist of: (1) studying the existing model for teaching speaking to find the weaknesses of the existing model for teaching speaking using observation, interview, and questionnaire; (2) developing a model for teaching speaking using cooperative learning (trying out the model in speaking class: observation and FGD); and (3) field testing the model to find out whether a model for teaching speaking using cooperative learning is more effective than the existing model for teaching speaking. The paper reveals the following: (1) the weaknesses of the existing model for teaching speaking are as follows: (a) it is dominated by lecturing which is boring and difficult to understand; (b) it is monotonous because of lack of various models or methods; (c) the topic is not interesting; (d) the task is mostly individual; (e) discussion is rarely used; (f) the students are passive; and (g) there is lack of speaking practices and exercises; (2) developing a model for teaching speaking using cooperative learning as follows: (a) planning: to choose the topic to speak by using think and talk in groups (TTW: think, talk, and write) or think in pairs (TPS: think, pair, and share); (b) outlining: to discuss in groups or pairs the main points which will be used to develop the topic; (c) drafting: to practice in groups or pairs developing the main points into dialogue, conversation, or role play; (d) revising/editing: using peer editing/exchange/correction or group work to check the mistakes in: content, organization, grammar, vocabulary, and pronunciation (all indicators of speaking skill); and (e) sharing: the group or pair presentation while the other groups and lecturer give comments and correction; and (3) a model for teaching speaking using cooperative learning is more effective than the existing model for teaching speaking because: (a) the students are more interested or motivated to speak in groups or pairs; (b) the students are more active working in groups or pairs; (c) the students are not ashamed to make mistakes; (d) the students learn from their peers and lecturer; and (e) it can develop all indicators of speaking.